1982
DOI: 10.1159/000153307
|View full text |Cite
|
Sign up to set email alerts
|

Pi<sup>Winneytown</sup>: New Alpha<sub>1</sub>-Antitrypsin Allele in an American Negro Family

Abstract: Alpha1-antitrypsin allele PiWinneytown is traced in the family of a black man whose serum exhibits the new phenotype Wfinneytown. Affected individuals show no signs of disease. This is the fourth α1-antitrypsin variant discovered in the local negro population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1985
1985
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Bioinformatics methods for such purpose fall into two groups: strategies that use sequence, structural data and physicochemical features, and methods that are based on network construction. The latter can provide the inherent characteristics of topological configuration of associated biological networks which is often disregarded by the former strategies 6 . In the present work, we used GPL570 which is a good platform to evaluate the expression level of lncRNAs in tumorigenesis 11 , 28 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bioinformatics methods for such purpose fall into two groups: strategies that use sequence, structural data and physicochemical features, and methods that are based on network construction. The latter can provide the inherent characteristics of topological configuration of associated biological networks which is often disregarded by the former strategies 6 . In the present work, we used GPL570 which is a good platform to evaluate the expression level of lncRNAs in tumorigenesis 11 , 28 .…”
Section: Discussionmentioning
confidence: 99%
“…However, several recent studies have indicated significance of other genes and signaling pathways in determination of overall survival (OS) of patients 2 , 5 . Among the recently appreciated genes in this regard are long non-coding RNAs (lncRNAs) 6 . These transcripts are involved in the regulation of fundamental cell survival pathways and have functional interactions with proteins and other non-coding RNAs that participate in the pathogenesis of breast cancer 7 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, another scarce variant PIPclifton was detected in some Berber groups. This variant, which had been reported in a North American population originated from sub-Saharan Africa (Hug et al, 1981), is often associated with immunoglobulin GM and Cγ haplotypes frequent in subSaharan African populations. Thus, it seems to be typical to these populations (Chaabani et al, 1986) and shows the presence of sub-Saharan African traces in the gene pool of North African populations.…”
Section: Aat Gene Variants and Their Use In Anthropological Investigamentioning
confidence: 74%
“…46,50,52,53 Furthermore, the significant cost of augmentation therapy (total healthcare cost range from $36,471 to $46,114), its short-term effect, and the lack of noninvasive therapeutic options for AATD patients Approximately 30 variants of alpha-1-antitrypsin had been described and named according to the electrophoretic mobility in 1981. 25 Seventy-five alleles have been identified at the protein and gene level, including 10 normal AAT alleles. 26 The Ml (Val213) variant is the most common (44-49%).…”
Section: Conventional Therapies: Why They Are Insufficientmentioning
confidence: 99%